Customer dissatisfaction and Electronic Word Of Mouth towards brand switching behavior to Wardah products: Ketidakpuasan Pelanggan Dan Electronic Word Of Mouth Terhadap Perilaku Beralih Merek (Brand Switching) ke Produk Wardah - Anisa, Nur Aini; Darim, Abu; Widawati, Etty; Kristia Gayatri, Vanda; Widjatmiko, Andri Gastri (Procedia of Social Sciences and Humanities, 2022)
This research is motivated by the current human needs are not only limited to the need for clothing, shelter, and food which is a priority, but the need for appearance by using cosmetic variants is also a need at this time. With this, there are many choices, especially for women, to choose products that provide benefits or satisfy their expectations. This makes the tendency of consumer behavior, namely the behavior of switching brands. The behavior of switching brands of cosmetic products occurs when the customer feels dissatisfied and there are other marketing factors, namely electronic word of mouth or the influence of word of mouth but occurs on social media. The population in this study were university students x who had switched brands to Wardah cosmetic products. The sampling technique in this study is non-probability sampling using purposive sampling with a sample size of 100 respondents. Testing the hypothesis of this study using multiple regression analysis with the help of SPSS. The results of the study indicate that there is an influence between customer dissatisfaction and electronic word of mouth, there is a behavior towards branding for Wardah brand cosmetics, either partially or individually and simultaneously or together. However, if there is no dissatisfaction and electronic word of mouth, then the behavior of switching brands to Wardah cosmetic products will not occur.